LINGUISTIC FEATURES OF ADDRESSING IN ENGLISH AND UZBEK - Almamatova Manzura Shavkatovna (Journal of new century innovations, 2022)
Annotation: In the article, on the material of the Uzbek and English languages, motivational statements are considered, expressing the forms of addressing familiarity and vernacular.